The Effect of Leisure Benefits on Leisure Satisfaction: Extreme Sports - Cihan Ayhan; Yasin Yıldız; Ersin Eskiler (Türk Spor ve Egzersiz Dergisi)
In this study, it was aimed to investigate the effect of leisure benefit on leisure satisfaction in extreme sports athletes. In order to determine the leisure satisfaction level of participants, Leisure Satisfaction Scale developed by Beard and Ragheb (1980) and adapted to Turkish by Gökçe and Orhan (2011) was used. Leisure benefit scale developed by Ho (2008) and adapted into Turkish by Akgül, Ertüzün, and Karaküçük (2018) was used to measure the perceived benefit from recreational activities. The conventional sampling method was used for sample selection, and a face-to-face survey method was used for data collection. Descriptive statistics, Pearson Correlation Analysis, and Regression Analysis were used in the analysis of obtained data. A total of 202 people (105 male and 97 female) participated in the study voluntarily. According to the results of the present study, it was determined that there was a positive significant relationship between Leisure benefit and Leisure satisfaction. In addition, it was determined that Leisure satisfaction was predicted by the sub-dimensions of Leisure benefit approximately 84%. This result showed that providing leisure benefits in extreme sports had a significant effect on Leisure satisfaction of extreme athletes.